Get Smart. Season 4 [videorecording (DVD)] - Brooks, Mel, 1926-; Henry, Buck (HBO Home Entertainment, 2016)
Season 4 includes 26 episodes of Get smart on 5 DVDs, including the legendary two-part special, "The not-so-great escape," featuring the agents' breakout from a sinister KAOS P.O.W. camp in New Jersey